The Relationship Between Religion and Public Schools in the United States: An Introductory Brief - Grinberg, Jaime (Advances in Social Sciences Research Journal, 2024)
The United States of America (USA) has no official religion, and its constitution establishes a separation between state and religion. Hence, public schools should maintain such a separation in their relationship to religion. However, historically, legally, and politically, this has been difficult, contentious, challenging, and complicated. Secularism has served as a balance to protect schools from religious intrusion and religion to keep the state from influence and control at bay. This paper briefly explains the seemingly watershed moment created by the US Supreme Court ruling enabling families in the state of Maine to obtain subsidies in the form of school vouchers to be applied toward tuition in religious private schools, thus breaking a legal tradition of denying public funds for their use for tuition covering of educational institutions sponsored by religious organizations. This paper introduces different dimensions for analyzing these relationships and explains a few legal and educational developments, legal rulings, and students’ rights.